Hazard identification and risk analysis in apron movement control services at Mopah Merauke airport - Sahupala, Peter (Universitas Muhammadiyah Metro, 2025)
Airside facilities that directly support aircraft operations include runways, taxiways and aprons. As far as possible, these facilities must be free from all forms of potential dangers and disturbances that could impact aircraft operations. The aim to be achieved is to determine the risk tolerance limit for each potential danger that exists on the Apron Movement Control service side at Mopah Airport by carrying out statistical analysis of each risk that may arise. Methods: The analytical method used is descriptive statistical analysis. Respondents were targeted at 50 (fifty) respondents specifically aimed at related parties, including: AMC Personnel, Regulators/Local Aviation Authorities, Mopah Airport Management, Commercial Airlines and Related Services at Mopah Airport which are closely related to the research. Results: The maximum score of respondents' responses to potential danger (Hazard) in the entire Apron Movement Control service activity at Mopah Merauke Airport is 125 with the highest potential in cleaning services and markings/signs on the side of the apron with a risk matrix of 1A, meaning there needs to be risk control/mitigation. which requires management decisions and the potential to be accepted after reviewing the implementation of operations. Conclusion: Mopah Merauke Airport's Apron Movement Control service activities are 125 with the greatest potential in cleaning services and markings/signs on the side of the apron. In this service activity, management decisions are needed in an effort to control the risk/mitigation of the existing potential and this potential can be accepted after reviewing implementation of operations.